LES study of turbulence intensity impact on spark ignition in a two-phase flow - Stempka, J.; Kuban, L.; Tyliszczak, A. (Archives of Mechanics, 2018)
The paper presents large eddy simulation (LES) study aiming at investigations of an influence of flow conditions on a spark ignition process in a two-phase shear dominated flow. Implicit LES approach is applied for the combustion modelling and the spark is modelled using the energy deposition model of Lacaze et al. [20]. We examine an impact of turbulence intensities and randomness of initial distributions of velocity fluctuations on a flame development during the spark duration and shortly after it is switched off. It is found that for a strong spark, as used in IC engines, the turbulence intensity has little effect on the ignition and flame kernel growth and no significant differences are seen even if the turbulence intensities differ four times. It is observed that weak turbulent structures cannot affect fast flame propagation mechanism and its development is conditioned by evaporation and rapid thermal expansion. In such regimes, the turbulence seems to be too weak to significantly alter the flame dynamics. It is found that at the initial stage of the flame development it grows toward the fuel-rich region and spread over the fuel-lean side only after the evaporated fuel diffuses and mixes with the oxidizer stream. The flame size and its shape turn out to be equally dependent on the initial distribution of the turbulence fluctuations and turbulence intensity.